Etika Berbusana dalam Penyiaran Televisi: Studi Kasus Penampilan Ivan Gunawan dalam Acara Brownis - Prameswari, Cucu Awaliyah; Dwi Marzein, Mentari; Sayidina, Grafika; Junaedi, Fajar (Jurnal Media Penyiaran, 2024)
Mass media, particularly television, plays a significant role in shaping public opinion and providing information to society. However, I the competitive race to capture viewer’s attention, ethical breaches in content presentation often occur. This study investigates such ethical violations, focusing on Ivan Gunawan’s controversial attire on the “Brownis” show aired by Trans TV. Using a qualitative descriptive method through observation and literature review, the research identifies significant breaches of decency and propriety norms as stipulated by the Indonesian Broadcasting Comission Broadcasting Behaviour Guidelines abd Broadcast Program Standards. The Indonesian Broadcasting Comission issued a formal written reprimand to the program for these violations. The findings emphasize the necessity for strict adherence to broadcasting regulations to uphold moral strandards and national identify. This study provides essential insight and guidelines for the broadcasting industry to enforce ethical dress codes, ensuring that content aligns with societal values and legal standards in Indonesia.